The geography of opportunity : race and housing choice in metropolitan America - De Souza Briggs, Xavier N. (Brookings Institution Press, 2005)
"A multidisciplinary examination of the social and economic changes resulting from increased diversity and their implications for economic opportunity and growth given persistent patterns of segregation by race and class, offering both public policy and private initiatives that would respond to those challenges"--Provided by publisher